Pengembangan Wall Chart Sejarah Pemberontakan DI/TII Jawa Barat - Moch. Nurfahrul Lukmanul Khakim; Abdul Fattah; Muhammad Lingga Andana; Putri Nur Fahriyanti (Criksetra: Jurnal Pendidikan Sejarah, 2021)
Teaching materials are needed in the process of delivering knowledge in the classroom so that the learning objectives are achieved following the curriculum used. One of the teaching materials prepared for the high school students on Indonesian History subject is the Wall Chart. This research method is the development of teaching materials ranging from analysis, design, development, implementation, and evaluation. This teaching material is about the struggle against the threat of rebellion such as DI/TII in West Java. The rebellion was initiated by an activist named S. M. Kartosuwiryo who was an Islamization figure who wanted Indonesia to become the Islamic State of Indonesia. The ideological difference between the Islamic group and the nationalist group triggered the rebellion. Based on the study of interesting Wall Chart teaching materials, it is useful to help the learning process of students so that they can understand historical material easily.